2009
DOI: 10.1124/dmd.108.023861
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Disposition of [14C]Bazedoxifene in Healthy Postmenopausal Women

Abstract: ABSTRACT:Bazedoxifene is a selective estrogen receptor modulator under development for the prevention and treatment of osteoporosis. The disposition of [ 14 C]bazedoxifene was determined in six healthy postmenopausal women after administration of a single oral dose of 20 mg (200 Ci). After dosing, blood was collected at frequent intervals, and urine and fecal samples were collected for up to 10 days. Aliquots of plasma, blood, urine, and fecal homogenates were analyzed for concentrations of radioactivity. Baze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 18 publications
1
38
0
Order By: Relevance
“…Several aspects of the disposition of BZA in rats appear to be similar those observed in post-menopausal women following oral administration (Chandrasekaran et al, 2009). The bioavailability after oral administration was low in both species: approximately 6% in women and 16% in rats.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Several aspects of the disposition of BZA in rats appear to be similar those observed in post-menopausal women following oral administration (Chandrasekaran et al, 2009). The bioavailability after oral administration was low in both species: approximately 6% in women and 16% in rats.…”
Section: Discussionmentioning
confidence: 86%
“…Following oral administration of a single 20-mg dose of [ 14 C]bazedoxifene to healthy post-menopausal women, the major route of excretion was the feces (84.7%), with only a minor fraction of the dose (0.8%) eliminated in urine; the predominant metabolic pathway was glucuronidation, with little or no cytochrome P450 metabolism (Chandrasekaran et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Bazedoxifene is rapidly absorbed50 with a t max of approximately 2 hours and exhibits a linear increase in plasma concentrations for single doses from 0.5 mg up to 120 mg. Following intravenous administration of a 3 mg dose of bazedoxifene, the volume of distribution is 14.7 ± 3.9 L/kg.…”
Section: Bazedoxifenementioning
confidence: 99%
“…41,42 Bazedoxifene is little metabolized by cytochrome P450, therefore risk of drug interactions is low. 43 Baird et al 44 evaluated the interaction between bazedoxifene 20 mg and 600 mg ibuprofen, and concluded that the use of two drugs together is safe and does not require dose adjustment.…”
Section: Metabolism and Pharmacokineticsmentioning
confidence: 99%